2014
DOI: 10.1155/2014/686791
|View full text |Cite
|
Sign up to set email alerts
|

Association of High Density Lipoprotein with Platelet to Lymphocyte and Neutrophil to Lymphocyte Ratios in Coronary Artery Disease Patients

Abstract: Background. We aimed to evaluate a relationship between platelet-lymphocyte ratio (PLR) and neutrophil-lymphocyte ratio (NLR) with high density lipoprotein (HDL) cholesterol levels in coronary artery disease (CAD) patients. Methods. A total of 354 patients with angiographically confirmed coronary blockages were enrolled in the study. Hematological indices and lipid profiling data of all the patients were collected. Results. We have observed significant association between HDL and PLR (P = 0.008) and NLR (P = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 32 publications
1
25
1
2
Order By: Relevance
“…In addition, NLR is associated with pro-inflammatory mediators (high sensitive CRP, tumor necrosis factor-α) and progressive subclinical atherogenesis [24].A high NLR is a predictor of atherosclerosis progression [10,25,26] and long-term prognosis in patients after PCI [12]. As a protective factor for blood vessels, HDL-C has been observed in both healthy people [14] and CAD patients [15] as associated with NLR levels at lower levels. However, few authors have focused on the relationship between variability in blood lipids and NLR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NLR is associated with pro-inflammatory mediators (high sensitive CRP, tumor necrosis factor-α) and progressive subclinical atherogenesis [24].A high NLR is a predictor of atherosclerosis progression [10,25,26] and long-term prognosis in patients after PCI [12]. As a protective factor for blood vessels, HDL-C has been observed in both healthy people [14] and CAD patients [15] as associated with NLR levels at lower levels. However, few authors have focused on the relationship between variability in blood lipids and NLR.…”
Section: Discussionmentioning
confidence: 99%
“…(18) As essential components of coronary thrombus formation, platelets play an important role in ACS. (2) In the CADILLAC study, increased platelet counts were also associated with restenosis and stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…(4) In their meta-analysis, Li et al showed that increased PLR is associated with in hospital and long-term mortality and cardiovascular events in ACS patients. ( (18) The combined use of NLR and PLR suggests that more prognostic information will be obtained. In this context, Choi et al found that combined NLR and PLR elevations were associated with long-term cardiovascular events (22).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 13,964 patients participating in twenty-six studies demonstrated that elevated platelet:lymphocyte ratio (plr) is a negative predictor for overall survival (os) with a hazard ratio of 1.60 [95% confidence interval (ci): 1.35 to 1.90; p < 0.01) 8 . High neutrophil:lymphocyte ratio (nlr) has also been shown to have poor prognostic implications in patients with chronic medical conditions such as coronary artery disease 9 and end-stage renal disease 10 . Utilizing prognostic indicators obtained from a complete blood count (cbc) to inform decision-making in patients with early-stage lung cancer considering sbrt is attractive, given that it is readily obtained, minimally invasive, and low cost.…”
Section: Introductionmentioning
confidence: 99%